Foundations of C++/CLI The Visual C++ Language for .NET 3.5 - Hogenson, Gordon (Apress : Imprint: Apress, 2008)
Foundations of C++/CLI: The Visual C++ Language for .NET 3.5 introduces C++/CLI, Microsoft's extensions to the C++ syntax that allow you to target the common language runtime, the key to the heart of the .NET Framework 3.5. This book gives you a small, fast-paced primer that will kick-start your journey into the world of C++/CLI. In 13 no-fluff chapters, Microsoft insiders take readers into the core of the C++/CLI language and explain both how the language elements work and how Microsoft intends them to be used. This book is a beginner's guide, but it assumes a familiarity with programming basics. And it concentrates on explaining the aspects of C++/CLI that make it the most powerful and fun language of the .NET Framework. As such, this book is ideal if you're thinking of migrating to C++/CLI from another language. By the end of this book, you'll have a thorough grounding in the core language elements together with the confidence to explore further that comes from a solid understanding of a language's syntax and grammar.